2017
DOI: 10.1073/pnas.1703424114
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Deepwater Horizon oil plume reveals substrate specialization within a complex community of hydrocarbon degraders

Abstract: The Deepwater Horizon (DWH) accident released an estimated 4.1 million barrels of oil and 10 10 mol of natural gas into the Gulf of Mexico, forming deep-sea plumes of dispersed oil droplets and dissolved gases that were largely degraded by bacteria. During the course of this 3-mo disaster a series of different bacterial taxa were enriched in succession within deep plumes, but the metabolic capabilities of the different populations that controlled degradation rates of crude oil components are poorly understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
78
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 47 publications
6
78
1
Order By: Relevance
“…In an experimental study Colwellia became a dominant taxon at an intermediate stage of hydrocarbon degradation (Hu et al 2017). The increase in abundance of this group was concurrent with an increased number of aromatic degradation genes as shown by metagenomic analyses and the decrease in the concentration of one -to three -ring aromatic compounds (Hu et al 2017).…”
Section: Ecology and Functional Traits Of Taxa Selected By Diatom-dommentioning
confidence: 98%
“…In an experimental study Colwellia became a dominant taxon at an intermediate stage of hydrocarbon degradation (Hu et al 2017). The increase in abundance of this group was concurrent with an increased number of aromatic degradation genes as shown by metagenomic analyses and the decrease in the concentration of one -to three -ring aromatic compounds (Hu et al 2017).…”
Section: Ecology and Functional Traits Of Taxa Selected By Diatom-dommentioning
confidence: 98%
“…For an example of lag times in an ocean microbial population sensing changing chemical energy opportunity, we can examine the elegant laboratory simulation of the Deepwater Horizon oil spill event by Hu et al (). Here the changes occurring over a 64‐day period in a series of stainless steel vessels containing sea water collected from the site and maintained at in situ temperature were followed both for the genomic patterns and the changing quantity of hydrocarbons present.…”
Section: The Rules Of Microbial Chemical Choicesmentioning
confidence: 99%
“…However, the 16S rRNA gene of Candidatus B. macondoprimitus does not match perfectly to any amplicons from the oil plume (Fig. 1A), and Hu et al (1) present no evidence to link the simulation to the environment beyond genus-level taxonomic community profiles.…”
mentioning
confidence: 94%
“…In their recent study, Hu et al (1) simulated in the laboratory the deep-sea oil plume of the Deepwater Horizon (DWH) disaster, and claim successful enrichment of the dominant oil-degrading bacteria found in the environment. Although the simulation offers valuable insights into microbial succession patterns following the addition of oil, our analysis revealed that the dominant hydrocarbon-degrading bacteria in the simulation was not in the environment, and the one in the environment was not in the simulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation